Amnesty International as a model of non-governmental organization and its contribution to improvement of the human rights - Abdülhakimoğulları, Erdal; Kedikli, Umut (Journal of Human Sciences, 2006)
As a result of the increasing numbers and powers of the non-governmental actors at economical, political and social areas in recent days, they have become an important issue to be analyzed. An important part of these actors which varies in context of activity fields and organization types, consists of Non-Governmental Organizations (NGOs). Because the importance of NGOs can not be denied in reinforcing the belief of states for being democratic and rule of law, the NGO’s which can act free from the states have a key role in protection and development of human rights. One of the important NGOs which attempt to protect and develop the human rights in international scale is definitely Amnesty International (AI). Being have a better understanding about the structure and activities of AI depends analyzing general structure and functions of NGOs. In this article firstly general features of NGOs, and their similarity and differences between other organizations have been analyzed; then the AI which organizes national and international activities with the purpose of generalizing the respect to human rights in universal level and therefore which is a Non-Governmental sivil society Organizaton whose activities gain a characteristic beyond the national borders has been analyzed.